Present time science philosophy - Сластенко, Є. Ф.; Синяков, С. В. (Proceedings of National Aviation University (archive), 1999)
Considered are the main tendency of developing recent philosophy and methodology of scientific cognition; made is the analysis of postpositivizm and social cognition